Whole-exome sequencing and bioinformatics analysis of a case of non-alpha-fetoprotein-elevated lung hepatoid adenocarcinoma - Yao, Yao; Guan, Xiaojiao; Bao, Guangyao; Liang, Jie; Li, Tian; Zhong, Xinwen (Frontiers in Pharmacology, 2022)
Hepatoid adenocarcinoma of the lung is an exceptionally rare malignant tumor with prominent Hepatocellular adenocarcinoma (HCC)-like characteristics in organs or tissue outside the liver, as while, there is no tumor in the liver. Most HAL cases have various degrees of serum alpha-fetoprotein (AFP) level and exhibit a similar origin and clonal evolution process to HCC. We studied a case of HAL without elevating AFP level by performing whole-exome sequencing (WES) and bioinformatics analyses after surgical resection. Our results showed mutations in two driver genes, NLRP3 and PBX1, and we identified HNRNPR, TP73, CFAP57, COL11A1, RUSC1, SLC6A9, DISC1, NBPF26, OR10K1 as potential driver mutation genes in HAL. In addition, 76 genes were differentially expressed in HAL tumor tissue versus para-cancerous tissue.